Transcatheter valve repair for tricuspid regurgitation: 1-year results from a large European real-world registry - Wild, Mirjam; Stolz, Lukas; Rosch, Sebastian; Rudolph, Felix; Goebel, Björn; Köll, Benedikt; von Stein, Philipp; Rottbauer, Wolfgang; Rassaf, Tienush; Beucher, Harald; Volz, Martin J.; Kassar, Mohammad; et al. (Journal of the American College of Cardiology, 2024)
Background - Tricuspid valve transcatheter edge-to-edge repair has emerged as a valuable treatment option for patients with severe tricuspid regurgitation (TR). - Objectives - This study aims to investigate the safety and effectiveness of the PASCAL transcatheter valve repair system in treating severe TR in a real-world patient population. - Methods - The PASTE (PASCAL for Tricuspid Regurgitation—a European registry) study is an investigator-initiated, multicenter, retrospective, and prospective observational cohort analysis conducted across 16 European heart valve centers including consecutive patients treated with the PASCAL transcatheter valve repair system from February 2019 to November 2023. Echocardiographic assessments were performed at baseline, discharge, and follow-up, and were subjected to centralized analysis. - Results - The study included 1,059 high-risk patients (mean age 79 ± 9 years; 53% female; TRI-SCORE risk 23% ± 18%; 87% NYHA functional class III/IV) with multiple comorbidities. Severe or higher graded TR was observed in 96% of patients. Intraprocedural success according to Tricuspid Valve Academic Research Consortium criteria was achieved in 85%, and TR reduced to ≤moderate in 87%. Independent predictors for a postprocedure residual TR of >moderate were coaptation gaps ≥8 mm (OR: 1.67; 95% CI: 1.03-2.72; P = 0.038), tenting height ≥10 mm (OR: 2.18; CI: 1.30-3.65; P = 0.003), the presence of a transvalvular lead (OR: 1.91; 95% CI: 1.19-3.05; P = 0.007), right ventricular dilatation >42 mm (OR: 3.35; 95% CI: 1.37-9.1; P = 0.009) and massive/torrential TR at baseline (OR: 4.59; 95% CI: 2.35-8.96; P < 0.001). At 1 year, 83% of patients showed ≤moderate TR. Significant clinical improvements included enhanced NYHA functional class (66% class I/II vs 17% at baseline; P < 0.001). Patients treated with the first-generation PASCAL system (n = 570) and with the new PASCAL Precision system (n = 489) had similar clinical profiles and TR severity at baseline. However, the Precision cohort showed greater TR reduction to trace/mild (63% vs 49%; P < 0.001), shorter procedure times (median 93 minutes [Q1-Q3: 69-130 minutes] vs 120 minutes [Q1-Q3: 82-165 minutes]; P < 0.001), and higher clinical success rates according to the Tricuspid Valve Academic Research Consortium at 30 days and 1 year (87% vs 81% [P = 0.021] and 56% vs 50% [P = 0.044], respectively). Higher center experience (≥21 patients/year) resulted in higher intraprocedural and clinical success. - Conclusions - The PASCAL system effectively treats severe TR in high-risk patients, offering sustained TR reduction and significant clinical improvements at 1-year follow-up.
Gesehen am 01.10.2025